Fabric ultraviolet light absorber composition and preparation method thereof

By using nanotitanium dioxide-grafted amino-terminated hyperbranched polymer as dispersant, the problem of unstable particle size of the UV absorber in the fabric under thermal storage conditions is solved, and the efficient thermal storage stability and anti-ultraviolet performance of the UV absorber are improved.

CN119843486AActive Publication Date: 2025-04-18SAIFEI (TIANJIN) NEW MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510346464.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-18
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

The UV absorber in existing fabrics is unstable in particle size under thermal storage conditions, affecting its UV absorption efficiency and compatibility with other materials.

Method used

Nanotitanium dioxide-grafted amino-terminated hyperbranched polymer is used as a dispersant, and combined with the UV absorber through physical adsorption or chemical bonding to form a stable adsorption layer, preventing particles from aggregating and maintaining uniform dispersion.

Benefits of technology

It improves the thermal storage stability of the ultraviolet absorber, maintains its good dispersion state and performance stability, and improves the resistance to ultraviolet rays and the thermal storage particle size stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of polymer auxiliaries, in particular to a fabric ultraviolet light absorber composition and a preparation method thereof. The invention relates to a fabric ultraviolet ray only absorbent composition which comprises the following raw materials in parts by weight: 20-50 parts of an ultraviolet ray absorbent, 6-13 parts of a dispersing agent, 0.3-0.8 part of a defoaming agent and 80-180 parts of water, wherein the dispersing agent is a nano titanium dioxide grafted amino-terminated hyperbranched polymer. The UPF value of the obtained ultraviolet light absorber composition can reach 40 + or even 50 +, the ultraviolet transmittance can reach 4.15-3.34%, the change rate of D90 can reach 25.64-21.24% after the heat storage time at 80 DEG C is changed from 20 min to 40 min, and the obtained ultraviolet light absorber is excellent in ultraviolet resistance and stable in heat storage particle size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer additives, and in particular to a fabric ultraviolet absorber composition and a preparation method thereof. Background Art

[0002] Ultraviolet rays are always present in our daily lives. Appropriate ultraviolet radiation is beneficial to the human body, but excessive exposure to ultraviolet rays will damage the human body and affect health. Textiles are the first line of defense to block ultraviolet radiation. It is particularly important to prevent excessive ultraviolet radiation and to carry out anti-ultraviolet finishing on textiles with poor anti-ultraviolet performance.

[0003] There are two main methods for anti-ultraviolet protection of fabrics: shielding method by improving the scattering and refraction of light through ultraviolet absorbers and improving the absorption of ultraviolet rays.

[0004] UV absorbers usually exist in the form of particles, and their particle size has an important influence on performance. Under hot storage conditions, the particle size will change, which may affect the UV absorption efficiency, compatibility with other materials, etc. Therefore, it is quite necessary to design a UV absorber with stable particle size during hot storage to improve the effect of UV. Summary of the invention

[0005] In order to improve the thermal storage stability of ultraviolet absorbers, the present application provides a fabric ultraviolet absorber composition and a preparation method thereof. In a first aspect, the present application provides a fabric ultraviolet absorber composition, which adopts the following technical solution.

[0006] A fabric ultraviolet absorber composition, comprising the following raw materials in parts by weight: 20-50 parts of ultraviolet absorber, 6-13 parts of dispersant, 0.3-0.8 parts of defoamer, and 80-180 parts of water; The dispersant is an amino-terminated hyperbranched polymer grafted with nano-titanium dioxide; The preparation method of the amino-terminated hyperbranched polymer grafted with nano-titanium dioxide is as follows: 1) Pretreatment of nano titanium dioxide The surface of nano-titanium dioxide is treated with a sodium hydroxide solution to introduce hydroxyl groups on the surface of the nano-titanium dioxide to obtain hydroxyl-nano-titanium dioxide; 2) Introducing active groups Using γ-glycidyloxypropyltrimethoxysilane to react with hydroxy-nano titanium dioxide, introducing epoxy groups on the surface of hydroxy-nano titanium dioxide to obtain epoxy-nano titanium dioxide; 3) Grafting reaction The epoxy-nano titanium dioxide and the amino-terminated hyperbranched polymer are mixed in a solvent, reacted at 80-100°C for 6-8h under the action of a catalyst, centrifuged and dried after the reaction, and the amino-terminated hyperbranched polymer grafted with nano-titanium dioxide is obtained. The weight ratio of the nano titanium dioxide to the amino-terminated hyperbranched polymer is 1:(0.5-0.7).

[0007] By adopting the above technical solution, the hyperbranched polymer is compounded with nano-titanium dioxide. The hyperbranched polymer has a highly branched structure and a large number of terminal functional groups, and can be combined with the ultraviolet absorber through physical adsorption or chemical bonding to provide good dispersion performance.

[0008] The amino-terminated hyperbranched polymer grafted with nano-titanium dioxide is used as a dispersant. The dispersant molecules are adsorbed on the surface of the ultraviolet absorber particles to form an adsorption layer with a certain thickness, forming a three-dimensional steric hindrance, preventing the particles from aggregating due to collision during the thermal storage process, maintaining its good dispersion state, and thus improving thermal stability. At the same time, the dispersant generates electrostatic charges on the surface of the ultraviolet absorber particles, causing the particles to repel each other. During the thermal storage process, this electrostatic repulsion can effectively prevent the particles from aggregating due to thermal motion, maintain the uniform dispersion of the particles, and ensure the stable performance of the ultraviolet absorber.

[0009] In addition, the amino-terminated hyperbranched polymer grafted with nano-titanium dioxide can reduce the surface tension between the UV absorber and the surrounding medium, making the UV absorber better wetted by water, and act as a bridge between the UV absorber and water, promoting the intermolecular interaction between them, so that the UV absorber and the medium are better combined. During the thermal storage process, phase separation or precipitation caused by incompatibility with the medium is avoided, and it can be more evenly dispersed in the medium when heated, reducing performance changes caused by excessive or low local concentrations, and improving thermal storage stability.

[0010] Furthermore, the preparation method of the amino-terminated hyperbranched polymer is: a) dissolving 3,5-diaminobenzoic acid in a solvent to obtain a 3,5-diaminobenzoic acid solution; b) adding a catalyst to the 3,5-diaminobenzoic acid solution, then heating to 120-150° C., reacting for 7-9 hours, and removing the water produced by the reaction by condensation reflux during the reaction; c) Cooling the reaction system to 50-80°C, then adding ethylenediamine, and continuing the reaction for 30-45 minutes to obtain a reactant solution; d) adding the reaction product solution dropwise into ether solvent to precipitate the polymer, and then filtering, washing and drying to obtain an amino-terminated hyperbranched polymer Furthermore, the weight ratio of the 3,5-diaminobenzoic acid to ethylenediamine is 1:(0.3-0.7).

[0011] Furthermore, benzophenone is grafted onto the amino-terminated hyperbranched polymer, and the grafting method is as follows: i. adding an amino-terminated hyperbranched polymer and glycidyl methacrylate to a toluene solvent, A catalyst is added, and the reaction is carried out at 80-100° C. for 8-12 hours to introduce double bonds into the hyperbranched polymer to obtain a double bond-amino terminated hyperbranched polymer; ii. reacting benzophenone with acryloyl chloride in the presence of triethylamine in dichloromethane to introduce an acryloyl group into the benzene ring of benzophenone to obtain a benzophenone compound containing a double bond; iii. The double bond-amino-terminated hyperbranched polymer obtained in i and the double bond-containing benzophenone compound obtained in ii are mixed, and then added to an organic solvent together with a free radical initiator, and a free radical polymerization reaction is carried out at 60 - 80 ° C in a protective gas atmosphere; iiii. After the reaction, the product was dialyzed and freeze-dried to obtain an amino-terminated hyperbranched polymer grafted with benzophenone.

[0012] Furthermore, the weight ratio of the benzophenone to the amino-terminated hyperbranched polymer is 1; (6-9).

[0013] Furthermore, the ultraviolet absorber is UV-326.

[0014] In a second aspect, the present application provides a preparation method for preparing a fabric ultraviolet absorber composition, using the following technical solution.

[0015] A preparation method for a fabric ultraviolet absorber composition comprises the following steps: S1. The ultraviolet absorber, dispersant, defoamer and water are mixed to obtain a pre-dispersion; wherein the amount of the defoamer is 1 / 2-2 / 3 of the total amount of the defoamer; S2. The pre-dispersed liquid is ground with the aid of a grinding medium; S3. After grinding, add the remaining defoamer and centrifuge to degas; S4. Filter to remove the grinding medium to obtain a suspension, which is sealed and stored away from light.

[0016] Furthermore, the grinding medium is glass beads, and the ratio of glass beads to pre-dispersion liquid is 1:(2-3) by volume.

[0017] In summary, this application has the following beneficial effects: This application uses a hyperbranched polymer and nano-titanium dioxide as a dispersant. The dispersant molecules are adsorbed on the surface of the ultraviolet absorber particles. During the heat storage process, phase separation or precipitation caused by incompatibility with the medium is avoided. When heated, it can be more evenly dispersed in the medium, reducing performance changes caused by excessive or low local concentrations, and improving heat storage stability. The UPF value of the obtained ultraviolet absorber composition can reach 40+ or ​​even 50+, the ultraviolet transmittance can reach 4.15-3.34%, and the D90 change rate can reach 25.64-21.24% after the heat storage time at 80°C changes from 20min to 40min. The obtained ultraviolet absorber not only has excellent anti-ultraviolet performance but also has a stable heat storage particle size. DETAILED DESCRIPTION

[0018] The present application is further described in detail below with reference to the embodiments.

[0019] Raw materials and intermediate preparation examples raw material UV absorber, UV-326; Defoaming agent, silicone defoaming agent; Nano-titanium dioxide, 200-300nm; γ-Glycidyloxypropyltrimethoxysilane, analytical grade; 3,5-Diaminobenzoic acid, analytical grade; Ethylenediamine, analytical grade; Diethyl ether, analytical grade; Glycidyl methacrylate, analytical grade; Benzophenone, analytical grade; Acryloyl chloride, analytical grade; Triethylamine, analytical grade; Dichloromethane, analytical grade; Free radical initiator, azobisisobutyronitrile.

[0020] Preparation Example Preparation Example 1 An amino-terminated hyperbranched polymer, the preparation method of which is as follows: a) Dissolve 1 kg of 3,5-diaminobenzoic acid in 10 kg of DMSO solvent to obtain a 3,5-diaminobenzoic acid solution; the dissolution temperature is controlled at 45°C, the magnetic stirring rate is 400 rpm, and the dissolution time is 45 min until the solution is clear; b) adding 10 g of p-toluenesulfonic acid catalyst to the 3,5-diaminobenzoic acid solution obtained in a), then heating to 135° C., condensing and refluxing under nitrogen protection, and reacting for 8 h; c) Cooling the reaction system to 60°C, then adding 0.5 kg of ethylenediamine and continuing the reaction for 40 minutes to obtain a reactant solution; d) The reaction product solution was added dropwise to an ether solvent at a volume ratio of 1:4, and allowed to stand for 3 hours to allow the polymer to precipitate, and then filtered, and washed three times with a 1:1 volume ratio of ethanol-water mixture and pure water to remove unreacted monomers and catalyst residues, and then washed and dried to obtain an amino-terminated hyperbranched polymer.

[0021] Preparation Example 2 The difference from Preparation Example 1 is that the amount of ethylenediamine used in step c) of Preparation Example 2 is 0.3 kg.

[0022] Preparation Example 3 The difference from Preparation Example 1 is that the amount of ethylenediamine used in step c) of Preparation Example 2 is 0.7 kg.

[0023] Preparation Example 4 The difference from Preparation Example 1 is that the amount of ethylenediamine used in step c) of Preparation Example 2 is 1.0 kg.

[0024] Preparation Example 5 An amino-terminated hyperbranched polymer grafted with benzophenone, the preparation method of which is as follows: i. In 55 kg of toluene solvent, 7 kg of amino-terminated hyperbranched polymer and 2 kg of glycidyl methacrylate were added, and 10 g of ‌4-dimethylaminopyridine catalyst was added, and the reaction was carried out at 90 ° C for 10 h under nitrogen protection to introduce double bonds into the hyperbranched polymer to obtain a double bond-amino-terminated hyperbranched polymer; ii. 1 kg of benzophenone was mixed with 0.5 kg of acryloyl chloride, 0.8 kg of triethylamine was added as an acid binding agent, and the mixture was reacted in 450 kg of dichloromethane solvent to introduce an acryloyl group on the benzene ring of benzophenone to obtain a benzophenone compound containing a double bond; iii. The double bond-amino-terminated hyperbranched polymer obtained in i and the double bond-containing benzophenone compound obtained in ii were mixed, and then added together with 0.5 kg of free radical initiator to 40 kg of toluene organic solvent, and free radical polymerization was carried out at 70 ° C in a nitrogen protective gas atmosphere for 8 hours; iiii. After the reaction, the mixture was dialyzed in deionized water for 48 h using a dialysis bag with a molecular weight cutoff of 4 kDa, with the water changed every 4 h. The mixture was then freeze-dried to obtain an amino-terminated hyperbranched polymer grafted with benzophenone.

[0025] Preparation Example 6 Different from Preparation Example 5, the weight ratio of benzophenone to amino-terminated hyperbranched polymer in Preparation Example 6 is 1:6, and the ratios of other raw materials remain unchanged.

[0026] Preparation Example 7 Different from Preparation Example 5, the weight ratio of benzophenone to amino-terminated hyperbranched polymer in Preparation Example 6 is 1:9, and the ratios of other raw materials remain unchanged.

[0027] Preparation Example 8 The preparation method of the amino-terminated hyperbranched polymer grafted with nano-titanium dioxide is as follows: 1) Pretreatment of nano titanium dioxide 1 kg of nano-titanium dioxide was ultrasonically dispersed in a 0.5 M sodium hydroxide solution, stirred at 80 °C for 2 h, centrifuged, washed with water until neutral, and dried to obtain hydroxy-nano-titanium dioxide; 2) Introducing active groups 1.2 kg of γ-glycidyloxypropyltrimethoxysilane and hydroxy-nano titanium dioxide were reacted in 50 L of anhydrous ethanol solvent at 70 ° C under nitrogen protection for 12 h, centrifuged and washed with ethanol, and dried in vacuum at 60 ° C to obtain epoxy-nano titanium dioxide; 3) Grafting reaction Epoxy-nano titanium dioxide and 0.5 kg of amino-terminated hyperbranched polymer from Preparation Example 1 were mixed in 30 L of toluene solvent, 30 g of triethylamine catalyst was added, and the mixture was reacted at 90° C. for 7 h. After the reaction was completed, the mixture was centrifuged and vacuum dried at 80° C. for 12 h to obtain an amino-terminated hyperbranched polymer grafted with nano-titanium dioxide.

[0028] Preparation Example 9 Different from Preparation Example 8, the amount of amino-terminated hyperbranched polymer used in Preparation Example 9 is 0.7 kg.

[0029] Preparation Example 10 Different from Preparation Example 8, the amount of amino-terminated hyperbranched polymer used in Preparation Example 10 is 0.8 kg.

[0030] Preparation Examples 11-13 Different from Preparation Example 8, the amino-terminated hyperbranched polymers in Preparation Examples 11-13 are from Preparation Examples 2-4, respectively.

[0031] Preparation Examples 14-16 Different from Preparation Example 8, the amino-terminated hyperbranched polymers in Preparation Examples 14-16 were replaced with equal amounts of amino-terminated hyperbranched polymers grafted with benzophenone from Preparation Examples 5-7, respectively. Example

[0032] Examples 1-3 A fabric ultraviolet absorber composition, the preparation method of which is as follows: S1. According to the raw material ratio in Table 1, the ultraviolet absorber, dispersant, defoamer and water are mixed to obtain a pre-dispersion; wherein the amount of the defoamer is 2 / 3 of the total amount of the defoamer; S2. Grinding the pre-dispersed liquid with the aid of glass bead grinding media, wherein the ratio of glass beads to pre-dispersed liquid is 1:3; S3. After grinding, add the remaining defoamer and centrifuge to degas; S4. Filter to remove the grinding medium to obtain a suspension, which is sealed and stored away from light.

[0033] Table 1 Raw material ratio table of Examples 1-3 (kg)

[0034] Wherein, the dispersant comes from Preparation Example 8.

[0035] Embodiment 4-11 Different from Example 2, the dispersants in Examples 4-11 are respectively from Preparation Examples 9-16.

[0036] Example 12 Different from Example 2, in Example 12, an equal amount of benzophenone is directly used as a raw material and mixed with the ultraviolet absorber.

[0037] Comparative Example Comparative Example 1 The difference from Example 1 is that the dispersant in Comparative Example 1 is the amino-terminated hyperbranched polymer obtained in Preparation Example 1.

[0038] Performance Testing With reference to "Evaluation of UV Protection of Textiles" GB / T 18830-2009, the UPF value and UV transmittance of the ultraviolet absorber composition obtained in the examples and comparative examples were tested; in a hot storage environment of 80°C, the hot storage particle size D90 of the ultraviolet absorber composition was tested after 20 minutes, and the hot storage particle size D90 of the ultraviolet absorber composition was tested again after 40 minutes, and the D90 change rate was calculated, D90 change rate = |60minD90-20minD90| / 20minD90*100%, the results are shown in Table 2.

[0039] Table 2 Performance test results

[0040] From Examples 1-12 and Comparative Example 1, and in combination with Table 2, it can be seen that the UPF value, ultraviolet transmittance and thermal storage stability of the ultraviolet absorber composition obtained in Examples 1-12 are better than those in Comparative Example 1, which indicates that the ultraviolet absorber composition obtained in the present application not only has a good ultraviolet absorption effect, but also has a stable thermal storage particle size.

[0041] Combining Example 1 with Comparative Example 1 and Table 2, it can be seen that the difference between Comparative Example 1 and Example 1 is the difference in dispersants. The UPF value, ultraviolet transmittance and thermal storage stability of the ultraviolet absorber composition obtained in Example 1 are better than those of Comparative Example 1, which shows that the ultraviolet absorber composition obtained in the present application not only has a good ultraviolet absorption effect, but also has a stable thermal storage particle size. This shows that the dispersant of the present application performs better in improving the absorption effect of the ultraviolet absorber and the thermal storage particle size stability. This may be because the amino-terminated hyperbranched polymer grafted with nano-titanium dioxide is used as a dispersant, and the dispersant molecules are adsorbed on the surface of the ultraviolet absorber particles, preventing the particles from aggregating due to collisions during the thermal storage process, and maintaining their good dispersion state. At the same time, the dispersant causes the particles to repel each other, maintains the uniform dispersion of the particles, reduces the surface tension between the ultraviolet absorber and the surrounding medium, makes the ultraviolet absorber better wetted by water, and acts as a bridge between the ultraviolet absorber and water, promotes the intermolecular interaction between them, and makes the ultraviolet absorber and the medium better combined. During the heat storage process, phase separation or precipitation caused by incompatibility with the medium is avoided, and it can be more evenly dispersed in the medium when heated, reducing performance changes caused by local excessive or low concentrations and improving heat storage stability.

[0042] Combining Example 2 with Examples 9-12 and Table 2, it can be seen that the use of benzophenone can improve the ultraviolet absorption effect of the ultraviolet absorber, but grafting benzophenone on the amino-terminated hyperbranched polymer can further improve the thermal storage stability of the ultraviolet absorber.

[0043] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A fabric ultraviolet absorber composition, characterized in that: The method comprises the following raw materials in parts by weight: 20-50 parts of ultraviolet absorber, 6-13 parts of dispersant, 0.3-0.8 parts of defoamer, and 80-180 parts of water; The dispersant is an amino-terminated hyperbranched polymer grafted with nano-titanium dioxide; The preparation method of the amino-terminated hyperbranched polymer grafted with nano-titanium dioxide is as follows: 1) Pretreatment of nano titanium dioxide The surface of nano-titanium dioxide is treated with a sodium hydroxide solution to introduce hydroxyl groups on the surface of the nano-titanium dioxide to obtain hydroxyl-nano-titanium dioxide; 2) Introducing active groups Using γ-glycidyloxypropyltrimethoxysilane to react with hydroxy-nano titanium dioxide, introducing epoxy groups on the surface of hydroxy-nano titanium dioxide to obtain epoxy-nano titanium dioxide; 3) Grafting reaction The epoxy-nano titanium dioxide and the amino-terminated hyperbranched polymer are mixed in a solvent, reacted at 80-100° C. for 6-8 hours under the action of a catalyst, centrifuged and dried after the reaction to obtain the amino-terminated hyperbranched polymer grafted with nano-titanium dioxide; The weight ratio of the nano titanium dioxide to the amino-terminated hyperbranched polymer is 1:(0.5-0.7).

2. A fabric ultraviolet absorbent composition according to claim 1, characterized in that: The preparation method of the amino-terminated hyperbranched polymer is: a) dissolving 3,5-diaminobenzoic acid in a solvent to obtain a 3,5-diaminobenzoic acid solution; b) adding a catalyst to the 3,5-diaminobenzoic acid solution, then heating to 120-150° C., reacting for 7-9 hours, and removing water produced by the reaction by condensation reflux during the reaction; c) cooling the reaction system to 50-80° C., then adding ethylenediamine, and continuing the reaction for 30-45 minutes to obtain a reactant solution; d) adding the reaction product solution dropwise into ether solvent to precipitate a polymer, and then filtering, washing and drying to obtain an amino-terminated hyperbranched polymer.

3. A fabric ultraviolet absorbent composition according to claim 2, characterized in that: The weight ratio of the 3,5-diaminobenzoic acid to ethylenediamine is 1:(0.3-0.7).

4. A fabric ultraviolet absorbent composition according to claim 2, characterized in that: Benzophenone is grafted onto the amino-terminated hyperbranched polymer, and the grafting method is as follows: i. adding an amino-terminated hyperbranched polymer and glycidyl methacrylate to a toluene solvent, A catalyst is added, and the reaction is carried out at 80-100° C. for 8-12 hours to introduce double bonds into the hyperbranched polymer to obtain a double bond-amino terminated hyperbranched polymer; ii. reacting benzophenone with acryloyl chloride in the presence of triethylamine in dichloromethane to introduce an acryloyl group into the benzene ring of benzophenone to obtain a benzophenone compound containing a double bond; iii. The double bond-amino-terminated hyperbranched polymer obtained in i and the double bond-containing benzophenone compound obtained in ii are mixed, and then added to an organic solvent together with a free radical initiator, and a free radical polymerization reaction is carried out at 60 - 80 ° C in a protective gas atmosphere; iiii. After the reaction, the product was dialyzed and freeze-dried to obtain an amino-terminated hyperbranched polymer grafted with benzophenone.

5. A fabric ultraviolet absorbent composition according to claim 4, characterized in that: The weight ratio of the benzophenone to the amino-terminated hyperbranched polymer is 1:(6-9).

6. A fabric ultraviolet absorbent composition according to claim 4, characterized in that: The ultraviolet absorber is UV-326.

7. A preparation method for preparing the fabric ultraviolet absorbent composition according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. The ultraviolet absorber, dispersant, defoamer and water are mixed to obtain a pre-dispersion liquid; wherein the amount of the defoamer is 1 / 2-2 / 3 of the total amount of the defoamer; S2. The pre-dispersed liquid is ground with the aid of a grinding medium; S3. After grinding, add the remaining defoamer and centrifuge to degas; S4. Filter to remove the grinding medium to obtain a suspension, which is then sealed and stored away from light.

8. A preparation method according to claim 7, characterized in that: The grinding medium is glass beads, and the ratio of glass beads to pre-dispersion liquid is 1: (2-3) by volume.

Citation Information

Patent Citations

  • Hyperbranched polyaramide functionalized graphene, as well as preparation method and applications of hyperbranched polyaramide functionalized graphene

    CN102826539A

  • Uvioresistant finishing agent and preparation method thereof

    CN105200784A

  • Preparation method of uvioresistant polyacrylate emulsion

    CN106283655A

  • Anti-ultraviolet bright plastic paint coating and preparation method thereof

    CN113072872A

  • Hyperbranched polyamide resin as well as preparation method and application thereof

    CN117229497A